Smart logistic adoption towards logistic performance - Wong, Soan Hank; Selamat, Atikah Saadah (Penerbit Universiti Teknikal Malaysia Melaka, 2023)
In this research, there are three aspect of smart logistic adoption that influence the logistic performance. The aspects are accessibility, reliability, and interoperability of smart logistic system. Technology Acceptance Model (TAM) was used as the framework in assisting the researcher by explaining and forecasting the technology users’ behavior. A survey was conducted to 111 respondents who works in an international logistics company located in southern part of West Malaysia.The research sampling design was the convenience sampling due to factor that employee such as delivery men are mobile and at different locations. With that, data was analyzed and interpreted in descriptive analysis to visualize the informationgathered. In the end, the result of relationship between aspect of smart logistic adoption and logistic performance are obtained, where accessibility and interoperability of smart logistics have significant relationship with the logistics performance.